2012
DOI: 10.15388/verb.2012.3.4973
|View full text |Cite
|
Sign up to set email alerts
|

ERASMUS Students Experiences in Linguistic Diversity and Multicultural Communication

Abstract: The promotion of students' mobility in the EU has had a huge impact in recent years in Lithuania, which has now become one of the countries with more students going abroad on an ERASMUS programme. Apart from being a means of studies and communication, languages offer access to cultural knowledge, diverse social and cultural identities and also contribute to cross-cultural communication both within Europe and with the rest of the world. The experiences gained while studying and living in another country give st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For example, Lipowski (2012) focused on problems of foreign Erasmus+ students studying in Poland and reported that main problems were related with the language barrier, cultural differences, the study program, the size of cities and the limited number of cultural events organized in English. A similar study was conducted in Lithuania by Užpalienė and Vaičiūnienė (2012) with the reflections of 20 Erasmus students from 13 countries. The qualitative study aimed to examine the experiences and the reflections of students studying and living in an environment which is culturally diverse and multilingual.…”
Section: Literature Reviewmentioning
confidence: 89%
“…For example, Lipowski (2012) focused on problems of foreign Erasmus+ students studying in Poland and reported that main problems were related with the language barrier, cultural differences, the study program, the size of cities and the limited number of cultural events organized in English. A similar study was conducted in Lithuania by Užpalienė and Vaičiūnienė (2012) with the reflections of 20 Erasmus students from 13 countries. The qualitative study aimed to examine the experiences and the reflections of students studying and living in an environment which is culturally diverse and multilingual.…”
Section: Literature Reviewmentioning
confidence: 89%
“…On the first hand, it allowed students to speak better English, a global language; on the other hand, it developed a real understanding of foreign language learning by being exposed to a second foreign language. Aydın (2012), Sigalas (2010), Teichler and Janson (2007), and Užpalienė and Vaičiūnienė (2012) have similarly concluded that the Erasmus Program is linguistically valuable in their research. Interview Participant #1 expressed the contribution of the program to the development of language skills as follows: Some people did not speak English in your work environment.…”
Section: Individual Developmentmentioning
confidence: 96%
“…Research on the experiences of Erasmus students shows the program provides a broad range of achievements for students. Students are being exposed into various learning experiences such as adaptation to different conditions, relations, and interaction with different cultures, new life experiences, and new opportunities through gaining attitude, knowledge, and skills (Mercer, 2011;Sigalas, 2010;Užpalienė & Vaičiūnienė, 2012). In a research work on the impacts and outcomes of academic mobility, Teichler (2001) found that mobility programs attributed to cultural enhancement, foreign language proficiency, and personality development and prepared students for professional life.…”
Section: Literature Reviewmentioning
confidence: 99%